Консолідований інформаційний ресурс офісної документації ПАТ «Іскра» - Голощук, Роман; Москалюк, Юлія (Видавництво Львівської політехніки, 2013)
The relevance of computer facilities while working with the office documents is discussed and the creation by designing a database for the office documentation using an Access software product, is proposed in this article. Also importance of creation of Internet web-site to provide access to company`s information resources for users is considered.
Keywords: information resource; database; quaries; registration of documents; website